Providing Assistance To Students At Al-Jabar Batam Private Vocational School - Dailami; Tito Pratama; Moh. Thandzir; Ilham, Wahyudi; Haufi Sukmamedian; y, Abd Rahmad (JURNAL KEKER WISATA, 2025)
Giving assistance is an action taken by individuals or organizations with the intention of assisting and benefiting those who are in need. This activity typically focuses more on social and humanitarian issues and is done freely without anticipating financial gain. Distribution of basic requirements (nine essential commodities) to disadvantaged individuals is one common way that assistance is provided. For those who cannot pay medical expenses, therapy is provided for free. instruction and practice to strengthen social skills. donations for those in need or those affected by natural calamities. cleansing the environment or engaging in other endeavors to enhance living standards. The primary goals of providing assistance are to lessen the pressures on others, foster a sense of fraternity among individuals, and foster a community that values others more. Typically, social institutions, neighborhood associations, or young people's groups that value cooperation carry out this activity.